2017
DOI: 10.1097/md.0000000000006126
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the role of IL-6 rs1800795 polymorphism in the susceptibility to prostate cancer

Abstract: Playing critical roles in immune responses, interleukin-6 (IL-6) has been proposed to be involved in the development of multiple cancers, including prostate cancer. The rs1800795 polymorphism in the promoter of the gene IL-6 can affect the transcription and expression of the gene, becoming a common target in association studies on tumors. We therefore carried out this meta-analysis to further discuss the relationship of this polymorphism with the risk of prostate cancer.Relevant publications were retrieved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…IL-6 activation of STAT3 seems to influence vital processes of tissue homeostasis maintenance. Thus, IL-6 gene regulates some of the key steps in controlling inflammation and establishes the anti-inflammatory environment (6)(7)(8). In this context, some studies have tried to understand how IL-6 is capable of protecting and resolving inflammation, but can also cause several harmful consequences to the organism, especially in chronic and progressive diseases (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 activation of STAT3 seems to influence vital processes of tissue homeostasis maintenance. Thus, IL-6 gene regulates some of the key steps in controlling inflammation and establishes the anti-inflammatory environment (6)(7)(8). In this context, some studies have tried to understand how IL-6 is capable of protecting and resolving inflammation, but can also cause several harmful consequences to the organism, especially in chronic and progressive diseases (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, to develop its functions in the biological control of processes, such as B cell differentiation, apoptosis, and cell proliferation, its membrane receptor (IL-6R) must be present. The IL-6/IL-6R complex activates important signaling pathways in inflammatory and carcinogenic processes (6)(7)(8)(9). When expressed, it may act as an anti-apoptotic factor in esophageal carcinoma cells by activating the STAT3 and JAK signaling pathway (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent meta-analysis have focused on the association between IL-6 promoter polymorphisms and cancer risk. Two meta-analysis showed that rs1800795 polymorphism increased the risk of prostate cancer and cervical cancer [ 108 , 109 ]. Though, the result same with ours, it still exist some problems.…”
Section: Discussionmentioning
confidence: 99%
“…And Duan et al reported that the -174 G/C polymorphism was a low-penetrance susceptibility variant for cervical cancer [ 19 ]. In addition, the IL-6 -174 G/C polymorphism reportedly enhances the susceptibility of African American men to prostate cancer [ 20 ].…”
Section: Discussionmentioning
confidence: 99%